2007
DOI: 10.1590/s0034-89102007000800004
|View full text |Cite
|
Sign up to set email alerts
|

Tendência da mortalidade por tuberculose no Brasil, 1980 a 2004

Abstract: OBJETIVO: Analisar o perfil atual e as tendências da mortalidade por tuberculose no Brasil, de 1980 a 2004. MÉTODOS: Estudo descritivo de tuberculose como causa básica ou associada de óbito do Brasil. Foram utilizados dados secundários do Sistema de Informação sobre Mortalidade. RESULTADOS: Houve redução inconstante do número e da taxa de mortalidade por tuberculose ao longo do período estudado, de 5,8 em 1980 para 2,8 por 100 mil habitantes, em 2004. Foi observada redução acentuada da mortalidade até 1985, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
10
0
10
Order By: Relevance
“…A tuberculose é mais frequente entre os homens que entre as mulheres 15,16,17,18 , assim como os óbitos pela doença 19,20 . No entanto, a não notificação dos óbitos no SINAN não foi associada ao sexo, como também foi observado na cidade do Rio de Janeiro 12 .…”
Section: Discussionunclassified
“…A tuberculose é mais frequente entre os homens que entre as mulheres 15,16,17,18 , assim como os óbitos pela doença 19,20 . No entanto, a não notificação dos óbitos no SINAN não foi associada ao sexo, como também foi observado na cidade do Rio de Janeiro 12 .…”
Section: Discussionunclassified
“…(2) In Brazil, there were 81,485 new TB cases in 2004, which corresponds to an incidence of 48.5 cases/100,000 population-with great regional variations-and the estimated mortality is 5,000 cases per year. (3) The state of Rio de Janeiro has the highest incidence of TB in the country: 87.5/100,000 population. In the city of Rio de Janeiro, this number increases to 105/100,000 population, reaching a much greater proportion in some pockets of poverty A nationwide epidemiological survey carried out by the Brazilian National Ministry of Health (NMH) from 1996 to 1997 showed that the rate of acquired resistance for the combination of isoniazid (INH) and rifampin (RMP) was 7.9%, whereas the rate of primary resistance was 1.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence and mortality of tuberculosis (TB) has decreased by approximately 20.0% and 30.0% respectively in Brazil in the last few decades, 2,6 around 80,000 cases and 4,000 deaths are still recorded annually in the country. 24,a As they are preventable, deaths from TB can be considered sentinel events, identifying failures in the health care systems, as well as assessing the control strategies employed.…”
mentioning
confidence: 99%